PERLINDUNGAN ANAK PENYANDANG DISABILITAS TERHADAP KEKERASAN SEKSUAL - Arianto, Iqbal Bimo Nur (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2022)
The study's goal is to identify the criminal penalties for those who commit sexual violence against children with disabilities, as well as the legal protections afforded to those children who are victims of such assault. Normative legal study was conducted, which examines the written law from a variety of angles but does not consider the practical implications of the law. Children with disabilities are afforded legal protection under Law no. 35 of 2014 pertaining to the protection of children, ensuring that they, like all children, are safeguarded and able to realize their full potential in terms of life, growth, and participation in a manner consistent with their inherent worth as human beings. There are currently no regulations governing criminal sanctions for those who commit violence against children with disabilities, but violators of Article 81 paragraph (I) of Law no. 35 of 2014 concerning Child Protection face prison terms of at least 5 years and no more than 15 years